HIGHER EXCITED STATES OF α+α SYSTEM - M. Odsuren; A.T. Sarsembayeva; G. Khuukhenkhuu; S. Davaa; K. Kato; B. Usukhbayar (Academic Scientific Journal of Computer Science, 2019)
In this work we investigate the higher excited states of + system applying the complex scaling method. The low-lying 0+ , 2+ and 4+ states of + are measured well but the higher excited states 6+ , 8+ and 10+ of + are not available by experimentally and these higher excited states have been barely studied by theoretical approaches.